A developmental study on the emergence of verb inflections among ESL low-intemediate learners - Rabiah Tul Adawiyah Mohamed Salleh (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2012)
This study is to show the developmental pattern of emergence of verb inflections among adult ESL learners, specifically on low-intermediate learners. Many previous studies have delved into this issue but unlike its predecessors, this study takes a very different approach; instead of using the conventional SOC approach to determine the sequence of emergence, this research opts for functional model. This approach is taken on the basis that it will expand the analysis of both the learners' targetlike and non-targetlike usage. The former approach (SOC) would only examine the targetlike usage of learners' output. Thus, for this purpose, 6 ESL low-intermediate students from UTM Semarak, Kuala Lumpur are chosen; these students are asked to write 4 inclass essays every 2 weeks as well as in a journal and their use of inflectional verbs are observed for a period of 10 weeks. Interestingly, at the end of the study, it is discovered that there is no similar sequence of emergence of English verbal inflections among the learners. The learners showed individual differences in their rates of attainment of the inflectional morphemes. It is then concluded that every learner's developmental acquisition of inflectional morphemes is unique and cannot be 'standardized' based on the overall emergent order of the samples.